Silica Nanoparticles Infused Mixed Matrix Membrane For Carbon Dioxide Removal Via Membrane Gas Absorption - Rosli, Aishah (2018)
Carbon dioxide (CO2) is the most produced, heat-trapping greenhouse gas and one of the main contributors to global warming. Membrane gas absorption (MGA) is a very attractive alternative for CO2 removal as it is simple, energy efficient, less space consuming and easy to scale up. However, major issues in MGA process are improving the membrane selectivity without reducing the permeability and membrane wetting, which can increase membrane mass transfer resistance significantly. Various materials with differing properties have been researched for the synthesis of MGA membranes to capture CO2, however, mixed matrix membranes (MMM) are proving to be a promising alternative, as the addition of inorganic particles into polymers opens the possibility of augmenting the membrane performance. In this work, polyvinylidene fluoride (PVDF) was chosen as the polymer matrix and fumed silica nanoparticles were incorporated into the polymer dope to produce MMM. A defect-free asymmetric membrane with both finger-like layer and sponge-like layer was successfully synthesised using 15 wt% polymer concentration with a casting thickness of 400µm in a coagulation bath of a mixture of ethanol and water. Among the three different silica nanoparticles investigated in this study, TS-530 silica nanoparticles that had been treated with hexamethyldisilazane gave superior CO2 absorption performance in MGA process in terms of selectivity and permeability of 22.5 and 1.9 x 10-4 mol/m2s respectively at 1 wt% silica loading. This improvement of selectivity of TS-530 MMM compared to pristine PVDF membrane, which had a selectivity of 7.18 could be due to the homogenous dispersion of the nanoparticles in the PVDF polymer matrix, effectively altering the structure of the membrane to increase membrane contact area, resulting in better selectivity of CO2 over nitrogen while hardly affecting the permeability. The performance of the MMM was further improved by adding a layer of low-density polyethylene (LDPE) coating on the membrane to increase its hydrophobicity and resistance to membrane wetting. The coated MMM proved to be better than the non-coated MMM in both permselectivity and sustainability in an extended run, with CO2 absorption flux and selectivity of 2.4 x 10-4 mol/m2 s and 22.8 respectively. A dynamic model was then proposed to simulate CO2 absorption in the MGA process, taking not only the gas solubility into the liquid absorbent into account, but also the gas solubility into the membrane. The model was found to be in good fit with experimental results, with R2 values exceeding 0.92. The optimum coated MMM with superior selectivity and better resistance to membrane wetting with liquid entry pressure of 13.55 bar and contact angle of 120° was used with the best operating parameters to observe the binary gas performance over an extended period. Throughout the study of the membrane synthesis, the potential membrane CO2 separation performance was observed in regards to a multitude of parameters and its resulting physical properties, which allowed for the monitoring of membrane performance under various influences.